Role of gasdermins in chronic kidney disease - Gao, Hanchao; Xie, Ting; Li, Yunyi; Xu, Zigan; Song, Zhuoheng; Yu, Huixia; Zhou, Hongming; Li, Weilong; Yun, Chen; Guan, Baozhang; Luan, Shaodong; Yin, Lianghong (Frontiers in Immunology, 2025)
Gasdermins (GSDMs), functioning as membrane perforating proteins, can be activated by canonical inflammasomes, noncanonical inflammasomes, as well as non-inflammasomes, leading to cell pyroptosis and the subsequent release of inflammatory mediators. Increasing evidence has implicated that GSDMs are associated with chronic kidney disease (CKD), including diabetes nephropathy, lupus nephritis, obstructive nephropathy, and crystalline nephropathy. This review centers on the role of GSDMs-mediated pyroptosis in the pathogenesis of CKD, providing novel ideas for enhancing the prognosis and therapeutic strategies of CKD.